PENGARUH CO-WORKER RELATIONSHIP, JOB MISMATCH, WORK-LIFE BALANCE TERHADAP JOB SATISFACTION DAN TURNOVER INTENTION - Heriyanto, Rossyta Eka Putri; Tanuwijaya, Justine; Wahyu Gunawan, Andreas (JURNAL ILMIAH EDUNOMIKA, 2024)
Business continuity in information technology services is starting to become a concern for many industries, along with these developments making employees look for job opportunities to be able to have a career in IT companies. In addition, employees who have the intention to change jobs consider several other factors. This study aims to analyze the effect of co-worker relationships, job mismatch, work-life balance on job satisfaction and turnover intention in Information and Technology Service Companies in West Jakarta. The data collection technique in this study was a questionnaire and library research. This study has a sample of 100 respondents which is the entire population of employees of an Information and Technology Services Company in West Jakarta using a saturated sampling technique as a sampling technique. Structural equation model (SEM) method with AMOS software version 22. The results of this research show that co-worker relationships have a positive effect on job satisfaction, job mismatch has no effect on job satisfaction, while work-life balance has a positive effect on job satisfaction, then job satisfaction has a negative effect on turnover intention.